Controlling the water matching technology and institutions in irrigation management in India and Nepal - Roth, Dik, 1954-; Vincent, Linden (New Delhi : Oxford University Press, 2013)
This work explores the means of controlling water for irrigation in India and Nepal. It looks at water sources and technologies in use and institutions evolving with them, and their adaptation under new policies and agrarian change. The various field studies conducted in India and Nepal document the complexities of water control in irrigation systems, and introduce concepts for their interdisciplinary analysis.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Includes bibliographical references.
Keywords: Irrigation -- India -- Management; Irrigation -- Nepal -- Management